The PID -5 Inventory: the dimensional profile of DSM5 to guide diagnosis and therapeutic needs in personality disorders. - Torres-Soto, Juan-F.; Moya-Faz, Francisco-J.; Giner-Alegría, Cesar-A.; Oliveras-Valenzuela, Maria-A. (Anales de Psicología / Annals of Psychology, 2018)
The PID-5 Inventory of the American Psychiatric Association evaluates personality and related disorders based on the dimensional trait model (DSM-5 Section III), which guides individual diagnosis and therapeutic needs. We analysed its usefulness as it was applied to patients that had been referred to a Day Hospital for Personality Disorders. In the sample of 85 subjects, 51 % had Borderline Personality Disorder (BPD), and 47 % had Personality Disorder NOS or Mixed (PD-NOS/MP), 65 % presenting comorbid clinical disorders. Among the BPD group, 89 % were women, 53 % were under 30 years old; they presented a PID-5 profile of greater severity, the Negative Affect and Disinhibition Domains stood out, as well as the facets of depression, impulsivity, anhedonia and distraction. Their borderline symptoms (BEST scale) were of greater intensity, they used fewer symptom coping strategies and more avoidance strategies (COPE-28 inventory). Among the PD-NOS/MP group, 58 % are women, 80 % were aged over 30 years, and negative affectivity, especially anxiety, stood out in their PID-5 profile. Both groups show borderline and avoidant features in the IPDE screening. The PID-5 was useful for confirming specific diagnoses (BPD), for describing the trait profile as well as proposing the specific therapeutic needs of both BPD and PD-NOS/MP patients.